Early Adversity and Critical Periods: Neurodevelopmental Consequences of Violating the Expectable Environment - Nelson, Charles A. (Trends Neurosci, 2020)
It is now widely recognized that children exposed to adverse life events in the first years of life are at increased risk for a variety of neural, behavioral and psychological sequelae. As we discuss in this paper, adverse events represent a violation of the expectable environment. If such violations occur during a critical period of brain development, the detrimental effects of early adversity are likely to be long-lasting. Here we discuss the various ways adversity becomes neurobiologically embedded, and how the timing of such adversity plays an important role in determining outcomes. We conclude our paper by offering recommendations for how to elucidate the neural mechanisms responsible for the behavioral sequelae and how best to model the effects of early adversity.